Probiotics intervention in preventing conversion of impaired glucose tolerance to diabetes: The PPDP follow-on study - Yan, Qun; Hu, Weiting; Tian, Yan; Li, Xu; Yu, Yuan; Li, Xing; Feng, Bo (Frontiers in Endocrinology, 2023)
Abstract Objectives: The purpose of this study was to assess the incidence of type 2 diabetes mellitus (T2DM) after 6 years in patients with IGT who received early probiotic intervention in the Probiotics Prevention Diabetes Program (PPDP) trial. Methods: 77 patients with IGT in the PPDP trial were randomized to either probiotic or placebo. After the completion of the trial, 39 non-T2DM patients were invited to follow up glucose metabolism after the next 4 years. The incidence of T2DM in each group was assessed using Kaplan-Meier analysis. The 16S rDNA sequencing technology was used to analyze gut microbiota's structural composition and abundance changes between the groups. Results: The cumulative incidence of T2DM was 59.1% with probiotic treatment versus 54.5% with placebo within 6 years, there was no significant difference in the risk of developing T2DM between the two groups (P=0.674). Conclusions: Supplemental probiotic therapy does not reduce the risk of IGT conversion to T2DM.